A study on the issues of the maintenance works during defect liability period for projects under Majlis Perbandaran Taiping / Marlia Abdul Wahab - Abdul Wahab, Marlia (Faculty of Architecture, Planning and Surveying, 2009)
This research was conducted to study on the issues of the maintenance work during defect liability period (DLP) for projects under Majlis Perbandaran Taiping, Perak. The research was commenced by introduction to all theory which are related to maintenance scope and furthered with the maintenance work in construction period. To more understanding the introduction regarding the DLP in each types of condition contract which is PWD 203 (2007), PAM 2006 and also CIDB 2000 based on the Standard of Form Contract which used in Malaysia has been discussed to know its meaning, who is person in charge during that period and all the responsible parties that involve during this stage. For the data analysis, it was collected via the interview with person who involved in maintenance works during DLP in each of case studies and also through the questionnaire distributed. The distributed questionnaires has been answered by various position of the construction industry people and also public people. All the data collected from the survey has been analysed and the finding was showed that there have a different view where was from questionnaire it shows that most of respondents choose the poor workmanship as a highest factor which may cause the defects during DLP while from the case studies it shows that the defect cause during that period more to third party liability’s fault. After the finding have recognized, some recommendations and approaches has been given in order to overcome the problem in each issues.